2022
DOI: 10.1002/adem.202270046
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolyzed Ultrasharp Glassy Carbon Microneedles

Abstract: Glassy carbon microneedles are pyrolyzed from polymeric microneedles that are synthesized by two‐photon polymerization lithography as described in the article number http://doi.wiley.com/10.1002/adem.202201222 by Jeffrey W. Kysar and co‐workers. They enable precise and controlled perforation of a guinea pig’s round window membrane that separates the middle ear and inner ear spaces. The perforations open a potential pathway for the delivery of therapeutics into the inner ear to treat hearing and balance disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The authors confirmed the validity of their device both in terms of safety and minimal invasiveness in several animal studies [ 48 , 49 , 50 ]. Additionally, this microneedle is available in metallic [ 53 ] and glassy carbon [ 54 ] versions.…”
Section: Procedures and Techniques For Perilymph Sampling Via A Micro...mentioning
confidence: 99%
“…The authors confirmed the validity of their device both in terms of safety and minimal invasiveness in several animal studies [ 48 , 49 , 50 ]. Additionally, this microneedle is available in metallic [ 53 ] and glassy carbon [ 54 ] versions.…”
Section: Procedures and Techniques For Perilymph Sampling Via A Micro...mentioning
confidence: 99%
“…To circumvent the current issues apparent in intracochlear administration, our laboratory has developed microneedles that allow for perforation of the RWM with minimal trauma and full reconstitution of the RWM structure within 72 h 19–24 . Several of these studies used an in vivo guinea pig model to assess the physiological consequences of perforation, aspiration, and injection through the RWM with follow‐up hearing studies between 0 and2 h, 48 h, 72 h, and 1 week post‐perforation.…”
Section: Introductionmentioning
confidence: 99%